FRI0244 Lysyl Oxidase as A Biomarker in Systemic Sclerosis– A Multicenter Study. (15th July 2016) - Rimar, D.; Balbir Gurman, A.; Meroni, P.; Farge, D.; Levy, Y.; Rosner, I.; Slobodin, G.; Jiries, N.; Rozenbaum, M.; Kaly, L.; Boulman, N.; Zilber, K.; et al.
Abstract : Background: Fibrosis and vasculopathy are the major concerns in systemic sclerosis (SSc), the pathogenesis of which is not clear. Lysyl oxidase (LOX) is an extracellular copper enzyme that cross-links collagen and elastin, thus stabilizing collagen fibrils [1]. In a preliminary study, LOX was found to be overexpressed in SSc patients and was suggested to be related to diffuse disease [2]. We evaluated skin and lung biopsies from 11 SSc patients and were able to show LOX located in the epidermis in the skin and in the endothelium of blood vessels within the dermis and in lung tissue. It is not clear whether the source of elevated LOX levels in SSc is damaged vascular endothelium or fibrotic tissues. Objectives: To evaluate LOX serum level of patients with SSc compared to patients with very early diagnosis of SSc (VEDOSS), patients with primary Raynaud's phenomena (PRP) and healthy controls in order to validate the elevated levels in SSc and to delineate its source. Methods: We prospectively evaluated patients for demographics, clinical manifestations and laboratory results including blood count, chemistry, urine examination, autoantibodies and serum LOX concentration determined by ELISA. We further evaluated lung function tests, echocardiography, lung high resolution CT scans, as needed, and determined lung involvement, modified Rodnan skin score (mRSS), Medsger disease severity scale and Valentini activity index [3]. Results: 86 SSC patients (76 women and 10 men) at a mean age of 49±12.4 were evaluated and compared with 110 patients with VEDOSS, 86 patients with PRP, and 80 age and gender matched healthy controls. Of the SSc patients, 42 had diffuse disease- 23 of them with lung fibrosis, and 44 had limited disease. LOX concentration in SSc was higher than VEDOSS, PRP and healthy controls, 12.8±7.5 ng/ml vs. 9.7±7.4 ng/ml vs. 8.1±5.4 vs. 8.9±5.1 ng/ml, respectively (p<0.0001). LOX level correlated with Medsger disease severity scale, correlation coefficients 0.24 (p=0.025) and inversely correlated with DLCO in patients with diffuse disease, correlation coefficients -0.35 (p=0.03). Age, duration of disease, mRSS, activity score, capillaroscopy pattern and pulmonary hypertension, did not correlate with LOX concentration. Conclusions: LOX level was found to be high in the serum of patients with SSc correlating with disease severity and inversely correlated with lung diffusion, suggesting a vascular source of LOX excretion in SSc. LOX was not elevated in patients with VEDOSS or PRP. Our study confirms our former observation of elevated LOX level in SSc and suggests LOX to be a possible biomarker of disease severity and vasculopathy in SSC. References: Csiszar K, et al. Lysyl oxidases: a novel multifunctional amine oxidase family. Prog. Nucleic Acid Res. Mol. Biol. 2001;70: 1–322. Rimar D et al. Brief report: lysyl oxidase is a potential biomarker of fibrosis in systemic sclerosis. Arthritis Rheumatol. 2014;66(3):726–30 Hudson M, et al. Update on indices of disease activity in systemic sclerosis. Semin Arthritis Rheum 2007;37(2):93–8. Disclosure of Interest: None declared